PROBLEMATIKA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI SD PLUS AL-ISHLAH BONDOWOSO - Ressi, Muhamad; Wahono, Suparwoto Sapto; Damiri, Madzkur (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2023)
The purpose of this research is to find out the problems that exist in learning Islamic Cultural History at SD Plus Al-Ishlah Bondowoso. In this study, researchers used descriptive qualitative research that emphasises the use of field data. The results of research conducted by researchers with a qualitative approach method and using data collection techniques with interviews, observations, and documentation on learning Islamic cultural history at SD Plus Al-Ishlah Bondowoso there are obstacles. Some of the obstacles experienced by educators and students in learning Islamic cultural history include; the lack of time allocation given to the subject of Islamic Cultural History, the method used by the Islamic Cultural History teacher is still monotonous, namely by using the lecture method, the diverse understanding of students in the learning process, and students cannot concentrate in receiving the material taught.